2021
DOI: 10.1101/2021.01.06.425575
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of water mobility in protein misfolding

Abstract: The propensity for intrinsically disordered proteins to aggregate is heavily influenced by their surrounding environment. Here, we show that the mobility of the surrounding water molecules directly influences the aggregation rate of α-synuclein (aSyn), a protein associated with Parkinson’s disease. We observe that the addition of NaCl reduces the mobility of water, while addition of CsI increases the mobility of water. In turn, this reduces and increases the mobility of aSyn, respectively, given the change in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…23,24 For example, it was reported that the stability of folded proteins in D 2 O differs from that in H 2 O, leading to different aggregation rates, 22,23,[25][26][27] especially in the brillation of amyloid proteins since water plays a key role in modulating the transition free energy of amyloid nucleation. [28][29][30] Furthermore, the use of D 2 O could result in substantial changes in the couplings between heavy water and protein vibrations due to the frequency shis of water bending and stretching modes upon H-D exchange, 31,32 which would alter the energy transfer and vibrational relaxation processes. Therefore, the IR spectroscopy of a protein in heavy water could differ from that in ordinary water, implying that an extra layer of caution is necessary when generalizing the IR spectroscopic results on protein folding-unfolding or aggregation processes in D 2 O.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 For example, it was reported that the stability of folded proteins in D 2 O differs from that in H 2 O, leading to different aggregation rates, 22,23,[25][26][27] especially in the brillation of amyloid proteins since water plays a key role in modulating the transition free energy of amyloid nucleation. [28][29][30] Furthermore, the use of D 2 O could result in substantial changes in the couplings between heavy water and protein vibrations due to the frequency shis of water bending and stretching modes upon H-D exchange, 31,32 which would alter the energy transfer and vibrational relaxation processes. Therefore, the IR spectroscopy of a protein in heavy water could differ from that in ordinary water, implying that an extra layer of caution is necessary when generalizing the IR spectroscopic results on protein folding-unfolding or aggregation processes in D 2 O.…”
Section: Introductionmentioning
confidence: 99%
“…Higher resolution TEM images further confirm that there is an increase in the number of SV binding to fibrils over time (Supplementary Figure 5), but also reveal that smaller SV or broken SV formed into blebs adhere to the aSyn fibrils, supporting the above SANS results of the disintegration of SV (Figure 1f, black arrows). The time scale of SV disintegration in the SANS experiments is faster due to the higher concentration of aSyn and SV used to produce higher scattering counts, but also due to the presence of D 2 O, which increases aSyn aggregation propensity 46 . We further show that, similar to our previous observations 2 , incubation of monomeric aSyn with SV leads to the formation of small clusters after 24 h (Supplementary Figure 6).…”
Section: Synaptic Vesicles Cluster In the Presence Of Monomeric Asyn ...mentioning
confidence: 99%